Agensifikasi dalam Pencegahan dan Penanganan Kekerasan Seksual di Universitas Sriwijaya - Amima, Sertin Agustina; Azhar, Azhar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to examine Sriwijaya University's aggressiveness in preventing and responding to sexual violence. The problem focuses on sexual violence committed by the academic community both verbally and audio-visually, in person or online. Sexual violence is an issue that has long developed in society, although some feel ashamed. Some victims feel that methods are close to what happened to them, and some also because they are under pressure. Since the development of this issue on social media and going viral in 2020 and 2021, the government has begun to take a role in efforts to prevent and handle sexual violence in the world of education, especially in the higher education environment with the existence of Permendikbudristek Number 20 of 2021. Sriwijaya University took the step of establishing aggressiveness as an implementer of the prevention and handling of sexual violence in its environment. With all the tasks and principles that must be carried out and respected. This research provides recommendations for Sriwijaya University to make more concrete and relevant regulations for the Sriwijaya University environment.